Midterm Results of Beating Heart Coronary Bypass Surgery for Non-left Internal Thoracic Artery Anastomosis According to Grafting Design and Implications of Intraoperative Flow Characteristics on Graft Patency - Lee, Seung Hyun; Chung, Cheol Hyun; Jung, Sung Ho; Lee, Jae Won; Choo, Suk Jung (The Thoracic and Cardiovascular Surgeon, 2012)
The aim of the present study was to investigate the midterm patency of coronary artery bypass grafting (CABG) surgery according to the grafting design and intraoperative flow characteristics. Between March 2007 and July 2008, 218 beating heart CABG patients were prospectively divided into two groups according to the non-left internal thoracic artery (LITA) bypass grafting design; Group I (n = 161, aorta–saphenous vein) and Group II (n = 57, LITA-radial artery composite grafting). Preoperative patient characteristics and the additive EuroSCORE were similar between the two groups (p = 0.82). Mean flow (mL/min) and pulsatility index were measured intraoperatively and coronary multidetector computed tomography (MDCT) was performed immediately and 1 year postoperatively. For the non-LITA bypasses, the mean flow was significantly greater in group I than in group II (27.9 ± 17.7 mL/min vs. 17.6 ± 12.6 mL/min, p < 0.001). Uni- and multivariate analysis showed the grafting design (group I) to be the only predictive factor for the favorable midterm patency of the non-LITA grafts (p < 0.001). There were no significant intergroup differences in the incidence of complications including that of stroke or death in the immediate postoperative period. A total of four patients had cerebral events: three in group I (1.87%) and one in group II (1.75%). The overall rates of freedom from graft occlusion for the non-LITA to LAD bypasses at 100, 200, and 300 days were 99, 98, and 89%, respectively, in group I, and 95, 88, and 70%, respectively, in group II (P < 0.01). Overall freedom from graft occlusion for LITA to LAD bypasses showed no significant differences between the two groups (98 vs. 93%, p = 0.053). The results suggest superior intraoperative flow characteristics of the direct aorta-saphenous vein bypass grafting design to be attributable for its favorable patency results.
Keywords: coronary bypass grafting; grafting design; intraoperative flow characteristics